2014
DOI: 10.1097/wnp.0000000000000030
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Neuromonitoring Alerts That Reverse With Intervention

Abstract: Intervention-mediated recovery from adversely changed evoked potential recordings may provide evidence for improved outcomes during neurophysiological intraoperative monitoring. However, these reversible signal changes (RSCs) are ambiguous because the patient's neurologic status cannot be known either at signal decline or after intervention. This article describes methods to reduce this ambiguity. Randomized control trials are not always possible or ethical. Recent thought on grading evidence has acknowledged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Several evidential limitations persist, among them: few controlled trials, paradox or bias in the categorization of recovered signal loss in observational studies, unsettled motor evoked potential alert criteria, and the unknowable confounders within and disagreement among recent supersized retrospective data sets. 4,32,38,46,54 Notwithstanding these limitations, the reliability of any future IONM outcome trials is threatened when the neurophysiologist's role is diminished or neglected. As already described within the interventional cascade, the surgeon's decision to change the course of surgery after an alert crucially depends on the credibility of the interpreter/communicator.…”
Section: Spine Ionm Evidence: Moving From Prediction To Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several evidential limitations persist, among them: few controlled trials, paradox or bias in the categorization of recovered signal loss in observational studies, unsettled motor evoked potential alert criteria, and the unknowable confounders within and disagreement among recent supersized retrospective data sets. 4,32,38,46,54 Notwithstanding these limitations, the reliability of any future IONM outcome trials is threatened when the neurophysiologist's role is diminished or neglected. As already described within the interventional cascade, the surgeon's decision to change the course of surgery after an alert crucially depends on the credibility of the interpreter/communicator.…”
Section: Spine Ionm Evidence: Moving From Prediction To Preventionmentioning
confidence: 99%
“…This PPV may seem low until one realizes that in a low prevalence context (risk ≤ 1% in extradural spine surgery, for example) the PPV will look low even when the test is very accurate. 20,54 Among the reviewed Class I studies, no false-negative reports were made. However, a prediction analysis that looks at differences in outcomes (no injuries with negative testing, 30% risk of serious injury with positive testing) incompletely informs us about the role IONM might play in injury prevention.…”
Section: Spine Ionm Evidence: Moving From Prediction To Preventionmentioning
confidence: 99%
“…There were no false positive or false negative results in our study. False positive results can lead to harmful and unnecessary treatment with economic burden (20,21). False negative results have not been reported frequently in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have demonstrated high sensitivity and specificity for detecting neurologic deficit, 10 11 which may be due to lack of preoperative neurologic deficit and cord compression and the defined period of intraoperative time where the risk for neural injury is high in these cases. 12 IONM of MEPs can be focused during the time of maximal manipulation of neural elements, such as during osteotomy closure. Likewise, IONM of MEPs is associated with very high sensitivity and specificity for spinal cord tumor surgery.…”
Section: Discussionmentioning
confidence: 99%